Interactive Manipulation of Nonconductive Microparticles in Scanning Electron Microscope by a Virtual Nano-Hand Strategy - Liu, Mei (Micromachines (Basel), 2019)
Micro/nano-manipulation is the fabrication of particular constructs on devices at the micro/nano-scale. Precise manipulation of microparticles is one of the key technological difficulties in manufacturing micro/nano-scale components. Based on scanning electron microscopy and nanomanipulator, this paper adopts a direct push method to operate randomly distributed microparticles into ordered structures. A two-probe interaction strategy is proposed to enable microparticle movements in all directions efficiently and avoid scratching the substrate surface. To overcome the uncertainties in micromanipulation, a virtual nano-hand strategy was also implemented: long-range advance of each microparticle is realized by multiple single-step pushes, whose trajectory is theoretically analyzed. The pushes are well programmed to imitate effects of a more powerful and determined hand. Experimental results show that the theoretical single-step motion trajectory is in line with actual operation, and the proposed strategy can ensure precise operation of the microparticles in all directions and improve reliability and effectiveness of operation.